Putative Riemerella anatipestifer Outer Membrane Protein H Affects Virulence - Gao, Qun; Lu, Shuwei; Wang, Mingshu; Jia, Renyong; Chen, Shun; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Huang, Juan; et al. (Frontiers in Microbiology, 2021)
Riemerella anatipestifer causes serious contagious disease in ducks, geese, and other fowl. However, as a harmful pathogen causing significant economic losses in the poultry industry, R. anatipestifer is still poorly understood for its pathogenesis mechanisms. In a previous study, we developed an indirect ELISA method for detecting R. anatipestifer infection using B739_0832 protein, a putative outer membrane protein H (OmpH) that is conserved among different serotypes of R. anatipestifer. Although OmpH in some pathogenic bacteria, such as Pasteurella, has been reported as a virulence factor, it is still not clear whether B739_0832 protein contributes to the virulence of R. anatipestifer. In this study, we confirmed that B739_0832 protein in R. anatipestifer localizes to the outer membrane. We constructed a B739_0832 deletion mutant strain (ΔB739_0832) and assayed various effects from the deletion of B739_0832. ΔB739_0832 strain had a similar growth rate to wild-type R. anatipestifer CH-1. However, the survival rate of ducklings in 10 days after infection from ΔB739_0832 strain was 50%, whereas no ducklings survived from wild-type R. anatipestifer infection. Furthermore, the median lethal dose (LD50) of the ΔB739_0832 strain was approximately 150 times higher than that of the wild-type strain. Pathology examinations on infected ducklings found that, at 36 h after infection, bacterial loads in blood, liver, and brain tissues from ΔB739_0832-infected ducklings were considerably lower than those from wild-type infected ducklings. These results demonstrate that the B739_0832 protein contributes to the virulence of R. anatipestifer CH-1.